The Needs Analysis of Luggage Handling System for Passenger Ferries at Jetty Kuala Perlis and Pulau Langkawi - Azila Ayub; Faisal Ikram Abd Samad; Puteri Zarina Megat Khalid; Rasidah Shafiee (International Journal of Supply Chain Management, 2018)
This study analyses the needs of luggage handling system for passenger ferries at both Kuala Perlis and Pulau Langkawi jetty. Both Kuala Perlis and Pulau Langkawi jetties currently adopt a conventional luggage handling system where passengers have to carry their own luggage or rent trolley to convey their possession from jetty to ferry checkpoint. The current practice is less reliable, time consuming and seems to burden ferry passengers. This study aims to identify a need, from customers view, to implement a new luggage handling system at the respective jetties. The new system would consist of the conveyor layout (from jetty to ferry), conveyor types and system, techno-economic aspects which will benefit both the passengers and ferry operators. A set of questionnaires was developed based on American Customer Satisfaction Index (ACSI) model which comprises Customer Expectation (CE), Perceived Quality (PQ) and Perceived Value (PV) as drivers of Customer Satisfaction (CS). The survey is distributed to a total number of 150 respondents who patronise the Kuah (Pulau Langkawi) and Kuala Perlis jetty. The data is analysed by using Statistical Package for Social Sciences (SPSS). The results indicate that there is a need for a new luggage handling system at the jetty.